Evaluation of the Therapeutic Outcomes of Antibiotic Regimen Against Carbapenemase-Producing Klebsiella pneumoniae: A Systematic Review and Meta-Analysis - Effah, Clement Yaw; Drokow, Emmanuel Kwateng; Agboyibor, Clement; Liu, Shaohua; Nuamah, Emmanuel; Sun, Tongwen; Miao, Lijun; Wang, Jing; Xu, Zhiwei; Wu, Yongjun; Zhang, Xiaoju (Frontiers in Pharmacology, 2021)
Background: Carbapenemase-producing Klebsiella pneumoniae (CpKP) has been implicated as an increasing threat to public health. CpKP is a ubiquitous, opportunistic pathogen that causes both hospital and community acquired infections. This organism hydrolyzes carbapenems and other β-lactams and thus, leading to multiple resistance to these antibiotics. Despite the difficult to treat nature of infections caused by CpKP, little has been discussed on the mortality, clinical response and microbiological success rates associated with various antibiotic regimens against CpKP. This meta-analysis was designed to fill the paucity of information on the clinical impact of various antibiotic therapeutic regimens among patients infected with CpKP. Materials and Methods: Literature in most English databases such as Medline through PubMed, Google Scholar, Web of Science, Cochrane Library and EMBASE, were searched for most studies published between the years 2015-2020. Data were analyzed using the R studio 2.15.2 statistical software program (metaphor and meta Package, Version 2) by random-effects (DerSimonian and Laird) model. Results: Twenty-one (21) studies including 2841 patients who had been infected with CpKP were analysed. The overall mortality rate was 32.2% (95%CI=26.23-38.87; I2= 89%; P-value ≤ 0.01). Pooled clinical and microbiological success rate were 67.6% (95%CI=58.35-75.64, I2= 22%, P-value= 0.25) and 74.9% (95%CI=59.02-86.09, I2= 53%, P-value= 0.05), respectively. CpKP infected patients treated with combination therapy are less likely to die as compared to those treated with monotherapy (OR=0.55, 95%CI= 0.35-0.87, P-value= 0.01). No significant difference existed between the mortality rate among 60years and above patients vs below 60years and among patients treated with triple therapy vs double therapy. Aminoglycoside-containing therapies when compared with aminoglycoside-sparing therapies had a positive significant outcomes on both mortality and microbiological success rates. Conclusion: New effective therapies are urgently needed to help fight infections caused by this organism. The effective use of various therapeutic options and the strict implementation of infection control measures are of utmost importance in order to prevent infections caused by CpKP. Strict national or international implementation of infection control measures and treatment guidelines will help improve healthcare, and equip governments and communities to respond to and prevent the spread of infectious diseases caused by CpKP.